DRIVE ORGANISATION DEVELOPMENT MODELIN ISLAMIC CHARACTER EDUCATION IN PRIMARY SCHOOLS IN KOPO SUB-DISTRICT - Dirjo, Dirjo; Rumbang Sirojudin; Ayatullah Humaeni; Ahmad Qurtubi; Wasehudin, Wasehudin (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
The purpose of this study was to determine the implementation of the development model of the Movement Organisation of the Institute for Education and Human Resources Development (LPPSDM) Bina Putera Utama in strengthening Islamic character education of elementary schools in Kopo District and its impact. The research method used is a qualitative approach, allowing researchers to explore in-depth descriptive data about the implementation of the model and its impact on strengthening Islamic character education in elementary schools in Kopo District. The results showed that the implementation of the model succeeded in increasing students' awareness and understanding of Islamic values in daily life. This is reflected in changes in students' attitudes and behaviours, such as being responsible, tolerant and caring for the environment, in accordance with Islamic teachings. With a focus on awareness, understanding and application of Islamic values, this model has brought significant changes in school culture, student behaviour and learning quality, all of which are crucial aspects in the formation of a solid Islamic character in students. In addition, the impact is felt in the visible changes in student behaviour, quality of learning, as well as parental involvement in the education process.